Optical Activation of the Dorsal Horn of the Thoracic Spinal Cord Prevents Ventricular Arrhythmias in Acute Myocardial Ischemia-Reperfusion Rats - Wu, Yong; Luo, Zhongxu; Hu, Zhengtao; Lv, Kun; Liu, Yinhua; Wang, Deguo (Frontiers in Cardiovascular Medicine, 2022)
Background and Objectives Spinal cord stimulation can prevent myocardial ischemia and reperfusion arrhythmias, but the relevant neurons and mechanisms remain unknown. Thus, this study applied optogenetic techniques to selectively activate glutamatergic neurons at the thoracic spinal cord (T1 segment) for examining the anti-arrhythmia effects during acute myocardial ischemic-reperfusion. Methods Adeno-associated viruses (AAVs) carrying channelrhodopsin-2 (ChR2, a blue-light sensitive ion channel) CaMKIIα-hChR2(H134R) or empty vector were injected into the dorsal horn of the T1 spinal cord. Four weeks later, optogenetic stimulation with a 473-nm blue laser was applied for 30 min. Then, the myocardial ischemia-reperfusion model was created by occlusion of the anterior descending coronary artery for ischemia (15 min) and reperfusion (30 min). Cardiac electrical activity and sympathetic nerve activity were assessed continuously. Results CaMKIIα-hChR2 viral transfection is primarily expressed in glutamatergic neurons in the spinal cord. Selective optical stimulation of the T1 dorsal horn in the ChR2 rat reduced the ventricular arrhythmia and arrhythmia score during myocardial ischemia-reperfusion, preventing the over-activation of cardiac sympathetic nerve activity. Additionally, optical stimulation also reduced the action potential duration at the 90% level (APD90) and APD dispersion. Conclusion Selective optical stimulation T1 glutamatergic neurons of dorsal horn prevent ischemia-reperfusion arrhythmias. The mechanism may be associated with inhibiting sympathetic nervous system overexcitation and increasing APD dispersion during myocardial ischemia-reperfusion.